2012
DOI: 10.1002/glia.22346
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Schwann cell differentiation and proliferation by the Pax‐3 transcription factor

Abstract: Pax-3 is a paired domain transcription factor that plays many roles during vertebrate development. In the Schwann cell lineage, Pax-3 is expressed at an early stage in Schwann cells precursors of the embryonic nerve, is maintained in the nonmyelinating cells of the adult nerve, and is upregulated in Schwann cells after peripheral nerve injury. Consistent with this expression pattern, Pax-3 has previously been shown to play a role in repressing the expression of the myelin basic protein gene in Schwann cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 61 publications
1
50
0
Order By: Relevance
“…studies have shown that Pax3 induces proliferation and inhibits apoptosis of Schwann cells (Doddrell et al, 2012) and also has a principal role in the regulation of dorsolateral melanocyte differentiation (Lang et al, 2005). Downregulation of Pax3 correlates with Oct6 and Krox20 (Egr2; early growth response 2) upregulation (which occurs at E17-P3) in promyelinating Schwann cells (Blanchard et al, 1996) and supports the supposition that Pax3 inhibits the myelination gene program (Kioussi et al, 1995;Doddrell et al, 2012).…”
Section: As In Vitro Primermentioning
confidence: 69%
See 2 more Smart Citations
“…studies have shown that Pax3 induces proliferation and inhibits apoptosis of Schwann cells (Doddrell et al, 2012) and also has a principal role in the regulation of dorsolateral melanocyte differentiation (Lang et al, 2005). Downregulation of Pax3 correlates with Oct6 and Krox20 (Egr2; early growth response 2) upregulation (which occurs at E17-P3) in promyelinating Schwann cells (Blanchard et al, 1996) and supports the supposition that Pax3 inhibits the myelination gene program (Kioussi et al, 1995;Doddrell et al, 2012).…”
Section: As In Vitro Primermentioning
confidence: 69%
“…Downregulation of Pax3 correlates with Oct6 and Krox20 (Egr2; early growth response 2) upregulation (which occurs at E17-P3) in promyelinating Schwann cells (Blanchard et al, 1996) and supports the supposition that Pax3 inhibits the myelination gene program (Kioussi et al, 1995;Doddrell et al, 2012). It is certainly intriguing to consider possible Pax3, Sox10, Mitf, Nrg1 (neuregulin 1), Igf1 and Pdgf gene regulatory networks that function in the specification of ISCs versus melanoblasts at this stage.…”
Section: As In Vitro Primermentioning
confidence: 71%
See 1 more Smart Citation
“…These pathways include Raf/ERK signaling and the transcriptional regulators Notch and c-Jun. Other transcription factors, like Notch and cJun, are characterized as negative regulators of myelination, including Sox2, Pax3, and Id4, are implicated in a similar function (Jessen and Mirsky 2008), as are the JNK and p38 MAP kinase pathways (Kioussi et al 1995;Le et al 2005;Mager et al 2008;Doddrell et al 2012;Hossain et al 2012;Yang et al 2012;DK Wilton, R Mirsky, and KR Jessen, unpubl. ).…”
Section: Control and Maintenance Of The Repair Phenotypementioning
confidence: 99%
“…In addition to the role of ERK1/2, recent data also indicate that the transcription factor Pax-3 has a role in differentiation and proliferation of Schwann cells after a peripheral nerve injury (Doddrell et al, 2012). Finally, and maybe of convincing importance, the transcription factor c-Jun, which is expressed in Schwann cells, seems to be a global regulator of the Wallerian degeneration process, since it may determine the expression of trophic factors, adhesion molecules, formation of regeneration tracks and myelin clearance as well as the control of distinct regenerative potential of the peripheral nerve.…”
Section: The Intrinsic Response In Neurons and Schwann Cells After Inmentioning
confidence: 99%